The EVER genes – the genetic etiology of carcinogenesis in epidermodysplasia verruciformis and a possible role in non-epidermodysplasia verruciformis patients - Kalińska-Bienias, Agnieszka; Kowalewski, Cezary; Majewski, Sławomir (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2016)
In recent years, the two adjacent novel EVER1 and EVER2 genes have been identified, whose mutations are responsible for the development of epidermodysplasia verruciformis (EV). Epidermodysplasia verruciformis is a rare, autosomal recessive genodermatosis associated with increased risk of skin carcinoma. Up to now 7 mutations in the EVER1 gene and 5 mutations in the EVER2 gene have been identified only in EV. It was also determined that the EVER genes belong to a novel gene family, the transmembrane channel-like (TMC) family, and are responsible for properly functioning zinc homeostasis. These observations have given new insights into EV pathogenesis.